DETERMINATION OF THE GALAXY CLUSTER ORIENTATION USING X-RAY IMAGES BY FOCAS METHOD - Shevchenko, S. Yu.; Tugay, A. V. (Одеські астрономічні публікації, 2017)
In our work we considered orientations of bright X-ray halos of the galaxy clusters (mainly Abell clusters). 78 appropriate clusters were selected using data from Xgal sample of extragalactic objects in XMM-Newton observation archive. Position angles and eccentricities of these halos were calculated applying FOCAS method. No privilegd orientations were found.